Роль елітарних якостей особистості у утворенні духовно-інтелектуального потенціалу нації - Шерстюк, Л.В. (Культура народов Причерноморья, 2002)
The article deals with the personality as a motive power in the creation of spiritual and intellectual potential of the nation. The author proves that students’ elite features formation in higher educational institutions is the main factor of society development.